2018
DOI: 10.1007/s11606-018-4647-8
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Mental Health Disorders and History of Unintended Pregnancy among Women Veterans

Abstract: Women Veterans with mental health disorders are more likely to have experienced any and greater numbers of unintended pregnancies than Veterans without mental health disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Women with psychiatric comorbidity also had increased likelihood of incident pregnancy despite lower likelihood of initiating contraception. Previous studies have shown that women with a history of mental health disorders are more likely to report unintended pregnancies than those without mental illness [ 36–38 ]. Furthermore, psychiatric comorbidities during pregnancy are associated with increased risk of pregnancy-related morbidity, as are unintended pregnancies [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women with psychiatric comorbidity also had increased likelihood of incident pregnancy despite lower likelihood of initiating contraception. Previous studies have shown that women with a history of mental health disorders are more likely to report unintended pregnancies than those without mental illness [ 36–38 ]. Furthermore, psychiatric comorbidities during pregnancy are associated with increased risk of pregnancy-related morbidity, as are unintended pregnancies [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study using survey data from ECUUN, women Veterans with self-reported mental illness diagnoses (including major depression, bipolar disorder, posttraumatic stress disorder, schizophrenia, and anxiety/panic disorder) were found to have similar rates of contraceptive use and method efficacy at last sex compared with Veterans without a diagnosis of mental illness. 41 These two studies together do not suggest that mental health diagnoses are a barrier to contraceptive access in the VA, which may reflect the strong integration of mental health services in primary care within the VA system. Questions remain regarding contraception for women with SUD, in part due to the limitations associated with identifying SUD with administrative data (the ECUUN study did not assess SUD).…”
Section: Vulnerable Populationsmentioning
confidence: 92%
“…3). 56 Mental health conditions have been linked to a variety of poor maternal and neonatal outcomes. Depression and PTSD are associated with increased risks of preterm birth, low birth weight, and postpartum depression [57][58][59] and poor infant outcomes such as respiratory failure and low birthweight.…”
Section: Mental Health and Psychosocial Factorsmentioning
confidence: 99%